Metastatic adrenocortical carcinoma: results of 56 pulmonary metastasectomies in 24 patients - Winkel, Jan op den; Pfannschmidt, Joachim; Muley, Thomas; Grünewald, Christiane; Dienemann, Hendrik; Fassnacht, Martin; Allolio, Bruno (The annals of thoracic surgery, 2011)
Background - Surgical resection is an important form of treatment for metastatic disease in patients with adrenocortical carcinoma (ACC). However, data about the results of this treatment are sparse. We reviewed our experience with the resection of pulmonary lesions metastatic from ACC as a means of evaluating such results. - Methods - A retrospective review of the database at a German national registry for ACC identified 24 patients (9 men and 15 women; median age, 41 years) who underwent pulmonary metastasectomy for primary ACC during the study period of 1989 through 2009. Only patients who met the criteria for potentially curative surgery, defined as the presumed feasibility of resecting all visualized tumorous lesions, were included. - Results - No perioperative deaths occurred in 56 pulmonary metastasectomies done on the patients in the study. The overall cumulative rate of 5-year survival, calculated from the time of first pulmonary surgery, was 24.5%, and the median survival was 50.2 months. Age younger than 41 years at the time of first pulmonary metastasectomy and repeated pulmonary metastasectomy were associated with longer survival in a univariate analysis. In accord with this, we observed a median survival of 31.9 months in patients 41 years of age or older as compared with a median survival of 59.3 months in younger patients (p = 0.004). In patients with repeated pulmonary metastasectomies, median survival after the first resection was significantly longer, at 59.3 months than in patients who had only one pulmonary resection, whose median survival was 31.9 months (p = 0.001). - Conclusions - We conclude that surgical resection of pulmonary metastases for ACC should be regarded as safe, with the potential for producing long-term survival in a highly selected group of patients. Younger patients may benefit more than older ones from such resection, and the recurrence of pulmonary metastases should not preclude repeated surgical resections of these lesions.
Gesehen am 09.05.2022